Accidental ingestion of hairpins in adolescent Muslim girls while doing or undoing the headscarf - Mir, Shakeel Ahmad; Dar, Hanief Mohamed; Dogra, Varun; Gilkar, Ishfaq Ahmed; Ahmad, Mir Mujtaba (International Surgery Journal, 2016)
Background: Recently there has been an increase in trends of aspiration and ingestion of sharp foreign body (pins) due to headscarf particularly in Muslim girls who have the habit of holding the pin between their lips or teeth, to get a free hand while doing or undoing their headscarf. The beaded end of the pin, is heavier than the rest of the pin and therefore the pin usually falls with beaded end pointing downwards. The objective of this study was to perform an epidemiological assessment of metallic hairpin ingestion in young Muslim females and stress on the need for a health education program in this population. Methods:This prospective study was done in the department of general Surgery in Government Medical College Srinagar over a period of one year from May 2014 to May 2015 and included all patients who presented with accidental ingestion of foreign bodies. Particular emphasis was given on accidental ingestion of headscarf pins in young adolescent Muslim females. Results:A total of 123 patients reported with foreign body ingestion, of which 75 (60.97%) had accidently ingested headscarf pins. Females outnumbered males comprising 83.74% of all patients who have ingested foreign bodies. Most of patients were in age group of 6-15 years. Hairpin ingestion was exclusively seen in females, comprising 75 (60.97%) of all patients who reported the department with ingestion of foreign bodies. 65 (86.67%) patients among hairpin ingestion group, were young adolescent females 11-20 years of age. All patients were admitted and Serial chest and abdominal X rays were taken. In 36 (48%) patients pin was successfully retrieved via Upper Gastrointestinal Tract Endoscopy. In 39 (52%) females, Upper Gastrointestinal Tract Endoscopic retrieval of the pin was not successful and patients were managed conservatively. 2 (2.66%) patients developed signs of peritonitis and emergency Laprotomy was done. There was one death (1.33%) in the study. Conclusion: The significant number of accidental ingestion metallic hairpins in young Muslim females highlights the need for a health education program in this population. Early upper gastrointestinal endoscopy remains the primary tool for retrieval of these foreign bodies.